New Bulgarian Rootstocks for Sour Cherry Cultivars (Prunus cerasus L.) - Dimitar Vasilev; Svetoslav Malchev; Lilyana Nacheva (Plants)
Research was conducted at the Agricultural Experiment Station—Khan Krum, Northeast Bulgaria during the period of 2014–2017. The aim of the study is to investigate the suitability of selected hybrids No.20-181 and No.20-192, obtained by interspecific crossing ‘Polevka’ (Prunus cerasus L.) × ‘Compact Van’ (Prunus avium L.) as clonal rootstocks for sour cherries. The rootstocks were grafted in a nursery with the cultivars ‘M-15’, ‘Nefris’, ‘Fanal’ and ‘Schattenmorelle’. Prunus mahaleb seedlings were used as the standard for comparison. Characteristics determining growth, the quality of the planting material and the compatibility of the rootstocks with commercial cultivars were tested. The average grafting success rate reported in the spring of the analyzed cultivar–rootstock combinations varied as follows: P. mahaleb (83–90%), hybrid No.20-192 (87–91%) and hybrid No.20-181 (82–85%). The selected hybrid 20-192 (‘Argo 2’) rootstock produces relatively weaker growth than the mahaleb. Hybrid 20-181 (‘Argo 1’) is characterized by the weakest growth. Both tested rootstock hybrids produce planting material with standard trunk diameter and tree height. With the weak growth that rootstock 20-181 induces in the grafted cultivar and the drought tolerance observed in 20-192, it is appropriate to continue the study in an orchard.